Pengaruh Proporsi Kendaraan Terhadap Kecepatan Arus Lalu Lintas: (Studi Kasus: Jalan Tgk. Chik Ditiro Depan Gedung Keuangan Banda Aceh) - Hidayat, Rifki; Shafira Niskhi, Aulya (University of Muhammadiyah Aceh, 2021)
Transportation is the movement of people or goods from one place to another using a vehicle driven by humans or machines. Along with its development, the number of vehicles in Banda Aceh is increasing. On the Tgk Chik Ditiro road, traffic jams often occur, because there are schools, offices, many traders who trade on the shoulder of the road and the sidewalk, there are several vehicles against the flow, and vehicles parked carelessly, there are delays or movement of traffic flow especially at the hour busy. Based on observations in the field, traffic flow at busy times is dominated by two wheels and four wheels, so that it affects the speed on the Tgk Chik Ditiro road in Banda Aceh City. The purpose of this research is to find out what percentage of the effect of the proportion of vehicles on road traffic flow and to get the value of the proportion of vehicles on the road. The results obtained for the highest traffic volume were obtained on Thursday 26 September 2019 at 17.00-18.00 amounting to 6669.60 pcu / hour, the value of road capacity was 4938 pcu / hour, while the level of road service with the degree of saturation obtained was 1.35 means the Jalan Tgk. Chik Ditiro Kota Banda Aceh is included in category F, where the flow is blocked, the speed is low, the volume is above capacity, and there is a delay. The results of traffic volume for 3 (three) days obtained the maximum proportion of two-wheeled vehicles on Thursday 26 September 2019 at 08.00-09.00 WIB with a value of 48.43%. For the Maximum Proportion of four-wheeled vehicles (LV) on Thursday 26 September 2019 at 17.00-18.00 WIB with a value of 74.77%. In the research, it can be seen that the dominant light vehicle growth affects these roads.